Navigating Ethical Quandaries in Nigerian Academia: A Conceptual Framework for Establishing Effective Research Ethics Boards and Ensuring Compliance - Oji, John; Alordiah, Caroline Ochuko (NIU Journal of Educational Research; Vol 10 No 1 (2024): NIU Journal of Educational Research, Vol. 10 No. 1, June 2024DO - 10.58709/niujed.v10i1.1939, 2024)
This study examines ethical issues in Nigerian higher education and offers a theoretical framework for setting up efficient research ethics committees and guaranteeing adherence. The first part of the study looks at the history of research ethics boards in Nigerian academia and their increasing necessity. In order to comprehend the significance of research ethics and pinpoint current frameworks for research ethics committees, a thorough literature analysis is carried out, with an emphasis on any shortcomings unique to Nigerian academia. A number of elements are included in the proposed conceptual framework, such as the definition and makeup of research ethics boards, the creation of mandates and scopes, the appointment and training of board members, the creation of ethical guidelines and policies, the application of ethical review procedures, and the cooperation with pertinent stakeholders. Furthermore, in order to improve the efficacy of research ethics boards, the framework highlights the significance of guaranteeing adherence to research ethics standards through awareness and education campaigns, ethical review procedures, ethical breach investigation and resolution, and regular evaluation. The discussion revolves around the potential consequences of putting the suggested conceptual framework into practice, which include improved research integrity, safeguarding research subjects, bolstering the reputation of the institution, fostering an ethical culture in research, improving research cooperation, and conformity to global norms. Many recommendations are made in light of the research and conclusions. These include cooperation with regulatory agencies, regular evaluation and improvement, networking and collaboration, institutional commitment, capacity building through training programmes, and awareness and education programmes. The importance of research ethics in Nigerian academia is emphasised in this study, which also offers a thorough conceptual framework for creating efficient research ethics boards. By putting this framework into reality, Nigerian universities would improve their standing in the eyes of the international academic community, improve research ethical procedures, and safeguard study participants. Keywords: Research ethics, Academic integrity, Research ethics boards, Compliance, Nigerian academia, Ethical guidelines, Ethical review processes